Baohuoside I Inhibits Osteoclastogenesis and Protects Against Ovariectomy-Induced Bone Loss - Ma, Min; Fan, Ao-yuan; Liu, Zheng; Yang, Li-qing; Huang, Jun-ming; Pang, Zhi-ying; Yin, Feng (Frontiers in Pharmacology, 2022)
The bone-resorbing osteoclast is essential for skeletal remodeling and hyperactive formation and function of osteoclast is common in bone metabolic diseases, especially in postmenopausal osteoporosis. Therefore, regulating osteoclast differentiation is a major therapeutic target in osteoporosis treatment. Icariin has shown potential osteoprotective effects. However, existing studies reported limited bioavailability of icariin and the material basis of icariin for anti-osteoporosis are attribute to its metabolites in body. Here, we compared the effect of icariin and its metabolites (icariside I, baohuoside Ⅰ and icaritin) on osteoclastogenesis by high content screening followed by TRAP staining and identified baohuoside Ⅰ (BS) with optimal effect. Then we evaluated the effect of BS on osteoclast differentiation and bone resorptive activity by both in vivo and in vitro experiments. In vitro study, BS could inhibit osteoclast formation and bone resorption function in a dose-dependent manner and the elevated osteoclastic-related genes induced by RANKL, such as NFATc1, Cathepsin K, RANK, and TRAP, were also attenuated following BS treatment. In vivo study, the OVX-induced bone loss could be prevented by BS through interrupting osteoclast formation and activity in mice. Furthermore, mechanistical investigation demonstrated that BS inhibited osteoclasts differentiation by ameliorating the activation of MAPK and NF-kB pathway and reducing the expression of uPAR. Our study demonstrated that baohuoside I could inhibit osteoclast differentiation and protect bone loss form ovariectomy.